2014
DOI: 10.1016/j.vaccine.2014.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the HPV-16/18 vaccine: Final according to protocol results from the blinded phase of the randomized Costa Rica HPV-16/18 vaccine trial

Abstract: Background A community-based randomized trial was conducted in Costa Rica to evaluate the HPV-16/18 AS04-adjuvanted vaccine (NCT00128661). The primary objective was to evaluate efficacy of the vaccine to prevent cervical intraepithelial neoplasia 2 or more severe disease (CIN2+) associated with incident HPV-16/18 cervical infections. Secondary objectives were to evaluate efficacy against CIN2+ associated with incident cervical infection by any oncogenic HPVs and to evaluate duration of protection against incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 38 publications
2
66
0
Order By: Relevance
“…18 A phase III randomized controlled study was conducted by the National Cancer Institute (NCI) of USA in the Guanacaste province of Costa Rica to evaluate the safety and efficacy of the bivalent vaccine in women aged 18 to 25 y 19 An ancillary posthoc analysis of the study evaluated the efficacy of fewer than 3 doses in the participants who received 2 doses (N D 422; 11.2% of the total participants) or a single dose (N D 196; 5.4% of the total participants) due to colposcopy referral, pregnancy, adverse events or non-compliance. 8 The vaccine efficacies against 12 months incident persistent HPV 16/18 infection after a median follow up of 4.2 y in the women negative for HPV 16/18 DNA at baseline were 80.9% (95% CI: 71.1 -87.7%), 84.1% (95% CI: 50.2 -96.3) and 100% (95% CI: 66.5 -100.0%) among the recipients of 3 doses, 2 doses and a single dose respectively.…”
Section: Efficacy Of Fewer Than 3 Doses Against Virological Endpointsmentioning
confidence: 99%
“…18 A phase III randomized controlled study was conducted by the National Cancer Institute (NCI) of USA in the Guanacaste province of Costa Rica to evaluate the safety and efficacy of the bivalent vaccine in women aged 18 to 25 y 19 An ancillary posthoc analysis of the study evaluated the efficacy of fewer than 3 doses in the participants who received 2 doses (N D 422; 11.2% of the total participants) or a single dose (N D 196; 5.4% of the total participants) due to colposcopy referral, pregnancy, adverse events or non-compliance. 8 The vaccine efficacies against 12 months incident persistent HPV 16/18 infection after a median follow up of 4.2 y in the women negative for HPV 16/18 DNA at baseline were 80.9% (95% CI: 71.1 -87.7%), 84.1% (95% CI: 50.2 -96.3) and 100% (95% CI: 66.5 -100.0%) among the recipients of 3 doses, 2 doses and a single dose respectively.…”
Section: Efficacy Of Fewer Than 3 Doses Against Virological Endpointsmentioning
confidence: 99%
“…Studies have consistently shown that HPV vaccines are highly immunogenic and effective in preventing HPV infections caused by the main oncogenic types and seem to have an excellent safety profile. Six large clinical trials (phase III) are classically cited as landmarks in the HPV vaccine literature, 3 of them for the 4-valent vaccine (FUTURE I, FUTURE II, and V501-020 study) [30-32], 2 for the 2-valent vaccine (Patricia Study and Guanacaste study) [33, 34], and one for the 9-valent vaccine (Broad Spectrum HPV Vaccine Study) [35]. All these trials were originally designed for women population, except the V501-020 Study [32], which included young men.…”
Section: Data From Clinical Trialsmentioning
confidence: 99%
“…The FUTURE, Patricia and Guanacaste studies showed that the 2- and 4-valent vaccines are effective in preventing precursor lesions in the uterine cervix (CIN, cervical intraepithelial neoplasia) [30, 31, 33, 34]. In the HPV-naïve women, the efficacy rates of both vaccines are higher than 90% but reduce to near 50% in the overall population.…”
Section: Data From Clinical Trialsmentioning
confidence: 99%
See 2 more Smart Citations